2017
DOI: 10.7324/japs.2017.70925
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol Overdose Induces Physiological and Pathological Aberrations in Rat Brain

Abstract: Paracetamol (Acetaminophen) is one of the most popular over the counter medications that is commonly used as an anti-inflammatory and pain killer, and to relieve fever and headaches. Despite its several therapeutic benefits, it is well known that an overdose of paracetamol can lead to hepatic and renal damage. Considering that brain cells is one of the main targets for paracetamol in the body, the effect of paracetamol on the physiology and histology of the brain is been poorly investigated. Hence, the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Our histological observation showed various degenerative alterations in different zones of rat hippocampus after acetaminophen treatment. These results coincided with an in vivo observations of Essawy et al who showed a harmful effect of this drug on the neurons of cerebral cortex in rats, in addition, this agent induces changes that indicate neuronal damage in granular cells of cerebral cortex (4). Acetaminophen is capable to activate the neuronal CYP2E1 thus producing toxic substances during metabolism as NAPQI (that decrease the level of glutathione and causing neurotoxicity and oxidative stress) (1), besides that, acetaminophen with overdose decreased the levels of anti-oxidants like glutathione, ascorbic acid with a relation to a significant reduction in the activity of superoxide dismutase (SOD).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our histological observation showed various degenerative alterations in different zones of rat hippocampus after acetaminophen treatment. These results coincided with an in vivo observations of Essawy et al who showed a harmful effect of this drug on the neurons of cerebral cortex in rats, in addition, this agent induces changes that indicate neuronal damage in granular cells of cerebral cortex (4). Acetaminophen is capable to activate the neuronal CYP2E1 thus producing toxic substances during metabolism as NAPQI (that decrease the level of glutathione and causing neurotoxicity and oxidative stress) (1), besides that, acetaminophen with overdose decreased the levels of anti-oxidants like glutathione, ascorbic acid with a relation to a significant reduction in the activity of superoxide dismutase (SOD).…”
Section: Discussionsupporting
confidence: 91%
“…Acetaminophen is capable to activate the neuronal CYP2E1 thus producing toxic substances during metabolism as NAPQI (that decrease the level of glutathione and causing neurotoxicity and oxidative stress) (1), besides that, acetaminophen with overdose decreased the levels of anti-oxidants like glutathione, ascorbic acid with a relation to a significant reduction in the activity of superoxide dismutase (SOD). The important over creation of reactive oxygen species (ROS) in brain and the imbalance between oxidative stress and antioxidants are related with pathologic alterations neurodegenerative disorders (4,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paracetamol, Acetaminophen (AMP), is one the first choice over the counter medication that is frequently used as pain killer and antipyretic [9,10]. AMP can cross the blood-brain barrier with a homogenous distribution in all brain areas [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in therapeutic intake, autophagosomes will engulf damaged mitochondria to eliminate malfunctioning mitochondria via mitophagy, reducing hepatocyte cell death. However, during paracetamol overdose, mitophagy becomes ineffective and hepatocyte cell death is enhanced due to cholesterol accumulaion in the lysosomal membrane [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%